Career portfolio training as a strategy to increase student competitiveness in the workplace - Fitriani, Nurul Amira; Mar’Atana, Agisna; Firdaus, Firdaus; Khotimah, Nurul; Hutapea , Parlindungan; Kurniawan, Eddy; Nur , Fatmawaty; Novakarti , Ovy; Sudagung , Adityo Darmawan; Alamri , Annisa Rizqa (Journal of Community Service and Empowerment, 2026)
This program aims to enhance the job readiness of D3 Office Administration students at the Faculty of Social and Political Sciences, Universitas Tanjungpura, by providing training on how to prepare professional career portfolios that align with industry requirements. The motivation behind this Community Service Activity (PKM) is the high unemployment rate in West Kalimantan, which reached 4.86% in August 2024. Notably, college graduates face even greater challenges in entering the workforce. National data shows that the unemployment rate for university graduates is 5.25%, higher than that of diploma graduates at 4.83%, with university graduates making up a significant portion of the educated unemployed. The program implementation employs a participatory and andragogical approach, comprising four stages: (1) situation and problem analysis, (2) program planning, (3) training implementation, and (4) activity evaluation. The activity took place on October 5, 2025, at SMKN 3 Pontianak, involving 67 first-semester students. The pre-test and post-test results indicated a significant increase in understanding across several areas: the importance of career portfolios (from 24.3% to 87.5%), the ability to compile a professional CV (from 24.3% to 87.5%), knowledge of digital platforms for career development (from 24.3% to 100%), and personal branding skills (from 20% to 87.5%). This program successfully raised awareness of digital career portfolios among students, developed training modules, and established a sustainable digital career learning community. Recommendations for the program include institutionalising career portfolio training as a regular annual initiative, integrating employability skills into the curriculum, and strengthening collaborations with industry to ensure the relevance of graduate competencies to current job market demands.